The autecology of Widdringtonia Cedarbergensis in relation to its conservation management - Manders, Patrick Timothy (Department of Biological Sciences, 2023)
The Clanwilliam cedar is an endangered tree species confined to the Cederberg mountains in the south-western Cape Province. An assessment of the current status of the species is presented as an introduction to the thesis. In the introduction inferences are made from the available evidence on the previous status of the populations. The present status is inferior to that prior to the influence of European settlers. Theories presented by previous authors to account for the decline are examined • A transition matrix model was developed, based on data from permanent monitoring plots, to model the population dynamics of the species. The methods of dealing with the data and fitting the observations to the transition matrix are presented. An eigenvalue of 1,01444 was calculated for the species, indicating population growth in the absence of fire. Inferences drawn from this model indicate that a minimum interval of 15 to 20 years between fires is necessary for the survival of the species . An analysis of habitat features obtainable from maps was used to define the general distribution range and the actual distribution of cedars within their range. Altitude is the major factor influencing both the general and actual distribution. Indirect evidence is presented in this analysis to indicate that cedars can grow over a far greater area within their present distribution range. Sowing experiments were conducted in the field to determine the effects of season of sowing and site features on germination success and seedling survival. Seeds sown in autumn exhibit the best combination of germination and establishment success. It is concluded that the Clanwilliam cedar can be successfully managed without detriment to the other species in the community and therefore warrants efforts for its conservation. Intervals of 15 to 20 years between prescribed burns are recommended on the grounds that cedar stands will be afforded sufficient time to recover from the mortality of the previous fire, especially with respect to seed production. At the same time, this interval should be short enough to preclude the occurrence of extremely intense wildfires and thus should prevent the associated high cedar mortality. Prescribed burns should be applied in late summer or autumn coinciding with the natural period of seed release. This will maximise the germination and establishment of the seed released from both the survivors and the trees killed. Where deemed necessary in terms of adult mortality or seedling recruitment, seed should be sown on selected sites as soon after a fire as possible. Cedar mortality will depend more on the conditions under which the prescribed burn is applied than on the season in which the burn is carried out.